AN ERROR ANALYSIS IN THE USE OF PAST TENSE IN WRITING RECOUNT TEXT AT THE SECOND YEAR STUDENTS OF SMP UNISMUH MAKASSAR (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
This research aimed to identify the kinds of error in the use of Past Tense in writing recount text and the dominant error made by the Second Year Students of SMP Unismuh Makassar. This research is Case Study Research. The research was conducted in SMP Unismuh Makassar. The population was the Second Year Students in Academic Year 2013-2014. The researcher took Class B1 which consists of 19 students.The instrument used was writing test. Writing test was used to find out the kinds of errors made by the students in writing recount text. By using this instrument, the researcher analyzed detail information about the errors in the use of Past Tense in writing recount text. The students' errors were classified into four categories based on the kinds of error. Those are the error of omition with 12 errors, error of addition with 31 errors, error of misformation with 166 errors, and error of misordering with 5 errors. The students made the dominant error in misformation category. It can be seen from the percentage result where misformation were 77,57%, then followed error of addition were 14,48%, error of omition was 5,61%, and misordering were only 2,34%. Based on these findings, it can be concluded that the Second Year Students(Class B1) of SMP Unismuh Makassar had many errors in writing recount text. The students should be given intensive exercises in the use of Past Tense in writing recount text.  It is quite necessary for the Second Year Students and the English Teacher of SMP Unismuh Makassar to be informed about the result of this research, so they can improve their teaching learning process.Keywords: Error Analysis, recount text, Past Tense, error of misformation.